KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN 3 UNDAAN LOR PADA MATA PELAJARAN MATEMATIKA SELAMA PEMBELAJARAN DARING - Naily Mufida; Irfai Fathurohman; Jayanti Putri Purwaningrum (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports how students’ critical thinking skills on KPK and FPB material during online learning at class IV of SDN 3 Undaan Lor Kudus. The research in this article is descriptive qualitative research. The subject of the research involved 5 fourth-grade students at IV SDN 3 Undaan Lor, which consisted of 3 male and 2 female students. The data were collected by using a test technique based on students’ critical thinking skills in the form of questionnaire form description and non-test techniques (observation, interviews, and documentation). The results indicated that (1) students’ critical thinking skills on KPK and FPB learning materials indicated an average value range of 68 with the moderate critical thinking skills criteria. (2) During the COVID-19 pandemic, face-to-face teaching and learning activities turned to online learning, so it was difficult for students to understand the learning material or assignments, which influenced the low students’ critical thinking skills. Many students had difficulty understanding the mathematics learning subject, especially on the KPK and FPB materials. The KPK and FPB learning materials should be explained directly because many students are still confused about how to determine KPK and FPB, and many students do assignments without noticing the right completion processes.